2008
DOI: 10.1007/s00424-008-0498-1
|View full text |Cite
|
Sign up to set email alerts
|

Physiology and pathophysiology of the vasopressin-regulated renal water reabsorption

Abstract: To prevent dehydration, terrestrial animals and humans have developed a sensitive and versatile system to maintain their water homeostasis. In states of hypernatremia or hypovolemia, the antidiuretic hormone vasopressin (AVP) is released from the pituitary and binds its type-2 receptor in renal principal cells. This triggers an intracellular cAMP signaling cascade, which phosphorylates aquaporin-2 (AQP2) and targets the channel to the apical plasma membrane. Driven by an osmotic gradient, prourinary water then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
201
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(204 citation statements)
references
References 252 publications
(286 reference statements)
1
201
0
2
Order By: Relevance
“…1994), and AVP binding to AVPR2 causes AQP2 to move to the basolateral surface of tubule cells. Hence, AVP increases the numbers of active (basolaterally expressed) and inactive (cytosolic) AQP2 (Boone and Deen 2008). For simplicity, we assume that both pools are affected equally by AVP, and that the effects track changes in AVP levels instantly.…”
Section: Curve Fittingmentioning
confidence: 99%
“…1994), and AVP binding to AVPR2 causes AQP2 to move to the basolateral surface of tubule cells. Hence, AVP increases the numbers of active (basolaterally expressed) and inactive (cytosolic) AQP2 (Boone and Deen 2008). For simplicity, we assume that both pools are affected equally by AVP, and that the effects track changes in AVP levels instantly.…”
Section: Curve Fittingmentioning
confidence: 99%
“…In renal principal cells, AVP regulates the expression of aquaporin-2 (AQP-2) water channel and its apical membrane insertion, leading to water reabsorption in the collecting duct and concentrated urine. 16 Two major effects of lithium on collecting duct-downregulating AQP-2 expression and reducing the number of renal principal cells-have been suggested to contribute to NDI. 4 Consistent with previous reports, 17 de Groot et al showed that lithium induced downregulation of AQP-2 both in cultured murine principal collecting-duct cells and in kidneys.…”
mentioning
confidence: 99%
“…In recent years, our understanding of the molecular nature of these transport proteins has made major progress through the application of functional expression cloning techniques using Xenopus laevis oocytes and the identification of gene defects in inherited renal tubular transport disorders. The regulation of these transport processes is constantly challenged by a demanding and greatly variable environment including an acidic luminal pH, a high medullary osmolarity, and a variability in blood and urinary flow as well as in the composition of the prourine [4]. The activity of these transporters can basically be controlled at several discrete levels.…”
mentioning
confidence: 99%
“…The largest fraction of the glomerular filtrate is retrieved in the proximal tubule that reabsorbs among others Na + , K + , Ca 2+ , Cl − , HCO 3 − , PO 4 3− , glucose, amino acids, and water. The Na + ,H + exchanger, one of the major luminal transporters, is accommodating many transport processes in this nephron segment.…”
mentioning
confidence: 99%
See 1 more Smart Citation